1H NMR spectra, structure, and conformational exchange of S-n-alkyl-tetrahydrothiophenium cations of some ionic liquids. (21st September 2022) - Hägele, Gerhard; Nazarski, Ryszard B.; Schmitz, Alexa; Xing, Shanghua; Janiak, Christoph
Abstract: S- n -alkyl-tetrahydrothiophenium cations [R-THT] + in some iodide or tetraphenylborate ion-pairs [R-THT][X] (R = methyl to n -decyl, X − = I −, [BPh4 ] −, [NTf2 ] − ) are characterized in the solid state by puckered THT rings in twist forms. In contrast, solution 1 H NMR spectra of compounds [R-THT][X] indicate a rapid conformational exchange leading to dynamic [ABCD]2 spin systems due to eight protons of the THT ring. These strongly coupled spectra obtained at high magnetic fields were analyzed by iterative methods and simulated successfully. In addition, molecular modeling and gauge-including atomic orbitals (GIAOs) based calculations of proton NMR chemical shifts for two such ion-pair compounds in solution were performed at the density functional theory (DFT) level . As a result, conformational equilibrium between two different pairs of isoenergetic twist forms of the THT ring in [Me-THT][I] (global and local energy minima) was found to exist. These theoretical results are discussed in view of experimental 1 H NMR spectral data. Graphical Abstract: UF0001